The Correlation between Visual Display Terminal (VDT) Use and Premature Presbyopia among The Office Workers - Amran; Dewi S. Soemarko; Umar Mardianto; Muhammad Ilyas; Julie D. Barliana (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Introduction: The increased use of Visual Display Terminals (VDTs) allows close work with continuous screen gazing during working hours. Close work forces the eyes to accommodate resulting in contraction of the ciliary system. This sustained contraction will lead to ciliary system weakness, making close work a risk factor for premature presbyopia. Methods: The research design was cross sectional. It was conducted on employees of health centers in Bekasi district who were under 40 years old with more than 1 year of service as employees and had used VDT for at least 1 year. Employees filled out an interview form voluntarily then the answers would be verified according to presbyopia and finally measured the amplitude of accommodation for respondents who met the presbyopia criteria. The research was carried out throughout December 2023. The collected data were statistically processed using the SPSS 26 application tool.Results: Of the 100 respondents who filled out the interview form and then verified and measured, 22 people (22%) had premature presbyopia. Age (p-value 0.014), type of VDT (p-value 0.049) and habit of working with VDT for 1 hour non-stop (p-value 0.016) were associated with premature presbyopia because they had a p-value <0.05. Based on multivariate test, the factor of working with 1 hour non-stop VDT was the only factor with p-value 0.018 and OR 3.78995% CI 1.255-11.445.Conclusion: There is an association of VDT use with the incidence of premature presbyopia in office workers by 22%. With the most significant influence owned by the factor of working with VDT 1 hour non-stop.